Women Empowerment through Tempeh Making Training from Melinjo Seeds in Cikumbueun Village, Pandeglang, Banten - Hilal, Samsu; Sodiq, Abdul Hasyim; Rumbiak, Julio Eiffelt Rossafelt; Amalina, Vidya Rizka (MOVE: Journal of Community Service and Engagement, 2025)
This research highlights the important role especially woman of housewives in fulfilling family nutrition and economic empowerment through creativity, especially in the utilization of local materials such as melinjo seeds. In Cikumbueun Village, the utilization of the abundant melinjo seeds as the basic ingredient for tempeh became the focus of training to improve the skills and welfare of housewives. The methods used included tempeh making, socialization, and evaluation through questionnaires. The results of the training showed a positive response from participants in terms of information delivery, availability of materials and tools, and understanding the steps of making melinjo tempeh. The training succeeded in increasing the creativity of housewives, providing new insights into the utilization of local food ingredients, and potentially improving the family economy through commercial marketing opportunities for tempe melinjo. The evaluation also showed an increase in participants' skills and economic productivity, as well as the potential for innovative product development from tempe melinjo. Thus, this training is effective in encouraging economic empowerment and food innovation based on local resources.